2020
DOI: 10.1108/ajeb-06-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, human capital and its impact on economic growth of emerging countries

Abstract: Purpose This paper aims to investigate the critical aspect of financial development, human capital and their interactive term on economic growth from the perspective of emerging economies. Design/methodology/approach Data set ranged from 2002 to 2017 of 83 emerging countries used in this research and collected from world development indicators of the World Bank. The two-step system generalized method of moments is used to conduct this research within the endogenous growth model while controlling time and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 49 publications
7
44
1
2
Order By: Relevance
“…Hence, low-income economies likely attain human capital development as a consequence of economic growth. The findings of this study are further supported by earlier studies such as Sarwar et al (2020), Giri (2014, 2017), Zaman et al (2012), Pradhan and Abraham (2002) and Zhang and Zhuang (2011). Overall, it is concluded that both financial indicators and economic growth are significant contributors to human capital in low-income countries.…”
Section: Estimations and Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, low-income economies likely attain human capital development as a consequence of economic growth. The findings of this study are further supported by earlier studies such as Sarwar et al (2020), Giri (2014, 2017), Zaman et al (2012), Pradhan and Abraham (2002) and Zhang and Zhuang (2011). Overall, it is concluded that both financial indicators and economic growth are significant contributors to human capital in low-income countries.…”
Section: Estimations and Resultssupporting
confidence: 88%
“…In low-income countries, it is apparent that financial development and economic growth is essential to improve human capital. Sarwar et al (2020) argued that countries with lower human capital stock levels required significant attention. Countries with a higher level of human capital can support those with a lower level of human capital.…”
Section: Introductionmentioning
confidence: 99%
“…MFI contributes to human development through six complementary tools such as education, job creation, income generation; women's empowerment; social and financial inclusion; and access to services (Arouri et al, 2014). Since then, human capital has been enhanced, contributing to sustainable development (Sarwar et al, 2021). Also, previous studies have been conducted to examine the relationship between financial development, economic growth and human capital for various countries (Sethi et al, 2019 for six selected South Asian economies; Maitra, 2018 for Bangladesh; Sehrawat & Giri, 2017 for ten selected Asian economies; Akhmat et al, 2014 for five South Asian Association for Regional Cooperation (SAARC); Nik et al (2013) for Iran; Bittencourt (2012) for four Latin American countries; Kendall (2012) for India; Chi (2008) for China; Shan and Morris (2002) for 19 OECD countries and China; Ranis et al (2000) for 76 developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We consider that studies on the link between financial development and human capital, leading to enhance and support economic growth in the emerging markets in the ASEAN, will provide important policy implications for policymakers. Sarwar et al (2021) consider that financial development and human capital positively and significantly affect emerging economies' economic growth. Sethi et al (2019) find that both the market size and financial development play an important role in developing human developing Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of FSD through institutional development supported a positive complementarity effects on growth ting strong institutions complemented FSD effects on Iheonu et al ( 2020) found among others that the impact of financial sector development on domestic investment depends on the measure of financial sector development utilized, banking intermediation efficiency and broad money supply negatively and significant influence domestic investment. Sarwar et al (2020) study indicates that financial development has a positive and significant effect on economic growth. In emerging countries, human capital also has a positive impact on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 97%